Studies in finance and development - the Gold Coast (Ghana) experience, 1914-1950 - Cox-George, N. A. (London : Dobson, 1973)
Economic or financial history of Ghana.
Includes index.
Bibliography: p. 213-214.
sju 22/01/2019
Loans
Keywords: Finance, Public; Ghana